The survival benefits of antiretroviral therapy in South Africa. - April, Michael D; Wood, Robin; Berkowitz, Bethany K; Paltiel, A David; Anglaret, Xavier; Losina, Elena; Freedberg, Kenneth A; Walensky, Rochelle P (The Journal of infectious diseases, 2014)
We sought to quantify the survival benefits attributable to antiretroviral therapy (ART) in South Africa since 2004.
Keywords: Adult; Analysis of Variance; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Computer Simulation; Cost-Benefit Analysis; Female; HIV Infections; Humans; Male; Middle Aged; Models, Theoretical; South Africa; Viral Load